Language Politeness in Valerie Patkar's Novel Serangkai: A Pragmatic Study - Khaulah Ghaida Muthmainah; Dedi Yusar; Prapto Waluyo (Universitas Pakuan, 2025)
This study aims to describe the forms of compliance and violation of language politeness principles based on Geoffrey Leech's theory of politeness in Valerie Patkar's novel Serangkai, as well as to identify the cultural context that emerges in the novel. The method used is descriptive qualitative with a pragmatic approach. Data collection was carried out using the free conversation technique, followed by the recording technique. The results of the study show data in the form of utterances that reflect compliance with the principles of polite language and data in the form of utterances that indicate violations of these principles. Compliance with the principles of politeness was found in six maxims, namely tact, generosity, approbation, modesty, agreement, and sympathy. Violations of the principles of politeness in language are found in six maxims, namely tact, generosity, approbation, modesty, agreement, and sympathy. This study also found a relationship between popular culture, language, and linguistic politeness. Keywords: popular culture, Geoffrey Leech, linguistic politeness, Serangkai novel, pragmatics